Przypadek martwicy kości szczęki po zastosowaniu chemioterapii Docetaxelem u 54-letniej pacjentki = The case of osteonecrosis of the maxilla after chemotherapy by Docetaxel in 54-year-old patient - Szczepkowska, Aleksandra; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Przypadek martwicy kości szczęki po zastosowaniu chemioterapii Docetaxelem u 54-letniej pacjentki = The case of osteonecrosis of the maxilla after chemotherapy by Docetaxel in 54-year-old patient. Journal of Education, Health and Sport. 2016;6(11):255-261. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166375 http://ojs.ukw.edu.pl/index.php/johs/article/view/3993 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 13.11.2016. Przypadek martwicy kości szczęki po zastosowaniu chemioterapii Docetaxelem u 54-letniej pacjentki The case of osteonecrosis of the maxilla after chemotherapy by Docetaxel in 54-year-old patient Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71 Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001 Streszczenie W pracy przedstawiono przypadek wystąpienia martwicy kości szczęki po zastosowaniu paliatywnej chemioterapii w leczeniu nowotworu piersi. Summary We report a case of osteonecrosis of the maxilla after the application of palliative chemotherapy for breast cancer. Słowa kluczowe: martwica kości, szczęka, chemioterapia Key words: osteonecrosis, maxilla, chemotherapy